Analysis of Sports Tourism Potential in Sumedang : an Implementation of MSPDM (Marketability, Sustainability, Participatory, Disaster Mitigation) - Rizal Ahmad Fauzi; Yudha Munajat Saputra; Amung Ma'mun; Nuryadi Nuryadi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Sports-based tourism can potentially be a tourism product that can provide high economic benefits for a region or even a country. Several types of sports tourism in Sumedang have the potential to be developed, but the local government needs to increase its budget for its development. The purpose of this study is to explore sports tourism, which has the most significant potential for the development of sports tourism, economic quality, regional image and human resources. The method used in this study is qualitative, with using the concepts of Marketability, Sustainability, Participatory, and Disaster Mitigation Management (MSPDM). The results of this study indicate that the marketing indicators of Golf are 100%, paragliding 93%, rafting 80%, and the rest are 50% - 60% each. In the sustainability indicator, paragliding is 96%, golf is 88%, rafting is 68%, and the rest is 48% -56%. In the participant indicator, paragliding 85%, rafting 70%, Golf 55%, and the rest 45% -50%. In the disaster mitigation indicator, paragliding is 100%, rafting is 90%, golf is 70%, and the rest is 40% each. The conclusion of this study shows that 3 potential sports tours were selected with the highest ranking, including Paragliding, Golf and Rafting.